Analisis High Density Polyethylene Berserat Bambu terhadap Kekuatan Tarik dengan Variasi Temperature Melting Komposit Polimer - Hutagaol, Laksana Putra; Lubis , Sobron Yamin; Siahaan, Erwin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to determine the effect of temperature on the tensile strength of polymeric materials that can have the strength used for HDPE with bamboo fibers. This study uses research methods and data collection will discuss starting from the manufacture of recycled HDPE plastic with bamboo fiber, then a Tensile test and Bending Test will be carried out to see the strength of the recycled results. The HDPE recycling process begins with collecting used plastic bottle caps made from HDPE which will be crushed before being put into the Hot Press Machine. Furthermore, the results of the crushing are put into the Hot Press Machine to be recycled into Panel Board Furniture. Based on the results of the test data obtained, it shows that (1) Variations in the addition of bamboo fiber particles to HDPE specimens affect the physical properties which causes the specimens to have a greater elastic modulus value than specimens without the addition of bamboo fiber particles to HDPE. This causes the stress value on the specimen to be greater, and the strain value to be smaller. (2) Pullouts are present in all types of specimens tested. Tensile which can be interpreted as a bond between the reinforced matrix and the matrix is not good or the bond between the bamboo fibers and the HDPE plastic is not fused. (3) The results of the tensile test show that the greater the temperature heated, the weaker the tensile strength will be. thus, the lower the temperature, the stronger the value of the tensile strength. This can be seen from the data from the tensile test results of the HDPE specimens.